Analisis Rasio Likuiditas dan Profitabilitas dalam Mnegukur Kineja Keuangan PT. Garuda Food Putra Putri Jaya Tbk yang Terdaftar di Bursa Efek Indonesia - Ria Anggita Zen. M; Angga Utama Marfito (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
The purpose of this research is to analyze the liquidity ratio and profitability ratio. The liquidity financial ratio is used to measure a company’s ability to immediately pay its current liabilities or debts, as well as its capability to generate profit from sales. The research was conducted using data obtained from the official website of PT Garuda Food Putra Putri Jaya Tbk and the Indonesia Stock Exchange, by examining the financial statements and financial performance from the years 2021 to 2024. The research method involved documentary data collection and literature study. The results of the financial performance analysis indicate that the company is in an unfavorable condition, as reflected in the financial ratios, which show that PT Garuda Food Putra Putri Jaya Tbk has not been able to generate the expected profit over four consecutive years and is also in a non-liquid state. Based on the liquidity ratio analysis, the Quick Ratio in 2021 was 0.81%, and it increased in 2022 and 2023 to 1.10%, indicating that the company was able to meet its short-term liabilities or current obligations. The Current Ratio in 2021 was 1.47%, rising to 1.74% in 2022, 1.78% in 2023, but then dropping to 1.37% in 2024. These results show that the company’s current ratio remains below the standard benchmark. The Cash Ratio was 0.51 or 51% in 2021 and increased to 0.60 or 60% by 2023. However, in 2024, it declined again due to an increase in total deposits while cash assets remained low.